Loss of endothelial cell-specific autophagy-related protein 7 exacerbates doxorubicin-induced cardiotoxicity - Albert Z. Luu; Vincent Z. Luu; Biswajit Chowdhury; Andrew Kosmopoulos; Yi Pan; Mohammed Al-Omran; Adrian Quan; Hwee Teoh; David A. Hess; Subodh Verma (Biochemistry and Biophysics Reports, 2021)
Doxorubicin (DOX) is an effective, broad-spectrum antineoplastic agent with serious cardiotoxic side effects, which may lead to the development of heart failure. Current strategies to diagnose, prevent, and treat DOX-induced cardiotoxicity (DIC) are inadequate. Recent evidence has linked the dysregulation and destruction of the vascular endothelium to the development of DIC. Autophagy is a conserved pro-survival mechanism that recycles and removes damaged sub-cellular components. Autophagy-related protein 7 (ATG7) catalyzes autophagosome formation, a critical step in autophagy. In this study, we used endothelial cell-specific Atg7 knockout (EC-Atg7−/−) mice to characterize the role of endothelial cell-specific autophagy in DIC. DOX-treated EC-Atg7−/− mice showed reduced survival and a greater decline in cardiac function compared to wild-type controls. Histological assessments revealed increased cardiac fibrosis in DOX-treated EC-Atg7−/− mice. Furthermore, DOX-treated EC-Atg7−/− mice had elevated serum levels of creatine kinase-myocardial band, a biomarker for cardiac damage. Thus, the lack of EC-specific autophagy exacerbated DIC. Future studies on the relationship between EC-specific autophagy and DIC could establish the importance of endothelium protection in preventing DIC.